Zooplankton of Munzur River (Tunceli, Turkey) - Saler, Serap (Medwell Online, 2011)
The zooplankton fauna of Munzur river was studied between June 2009 to May 2010. A total of 11 taxa were recorded. Out of these 8 species belonging to rotifera 2 to Cladocera 1 to Copepoda were recorded. The most species of zooplankton were found in June and July (11 species) while the minimum species were found in January (1 specie). Most of the zooplankton species were belonged to Rotifera. Also, it was found that the most common family in the study area was belonged to Brachionidae (4 species). All zooplankton species identified are considered as new record for Munzur river.
Keywords: Zooplankton rotifera; copepoda; cladocera; Munzur river; water quality; pollution level